ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER PADA NOVEL “9 MATAHARI” KARYA ADENITA - Muthia Hasna Harmanti (IKIP Siliwangi, 2020)
The novel is one of the literary works written by the author based on oneself or the experiences of others. Novels are liked by many people because there are moral values that are useful for daily life. The moral value is related to character education which has always been considered important for social life. Character education is often considered trivial because the delivery is not as clear as the delivery of formal education. In the novel